Alloys with Pt-skin or Pt-rich surface for electrocatalysis. (June 2018) - Li, Jing; Li, Li; Wang, Min Jie; Wang, Jianchuan; Wei, Zidong
Graphical abstract: Highlights: The feature of Pt-skin structured catalysts is derived from the ligand effect and geometric effect. The controlled tuning of surface and near-surface structures for Pt-skin catalysts is available. Manipulation of strain effect well improves electrocatalytic performance of Pt-skin catalysts. Abstract : The Pt-based alloys with Pt-skin or Pt-rich surface own significant structural advantages for a range of electrocatalytic reactions. Herein, we give a minireview for such catalysts, which covers a brief background introduction, the mechanisms for the activity enhancements derived from the special Pt-skin structures, the very recent advances on the preparation routes and applications of the catalysts in various electrochemical reactions, and a future perspective. Indeed the Pt-skin structured catalysts have shown great promising which in the future, may provide more opportunities for enhancing electrocatalytic performance at the molecular level.